ANALISIS PERGESERAN BAHASA PADA MASYARAKAT DESA DOLOK KAHEAN KABUPATEN SIMALUNGUN - Dhea Amalia; Azwa Khalisa Nasution; Safinatul Hasanah Harahap (JURNAL ILMIAH RESEARCH STUDENT, 2023)
Language contact that occurs in multilingual communities causes various linguistic events. This is one of the language shift events that occurred in the village of Dolok Kahean. In this case, a person or group of people abandons their first language or guyup language and switches to using a second language. Language Shift in the Community of Dolok Kahean Village, Simalungun Regency aims to show how language is used in this community in several age groups, namely children, teenagers and adults. The type of research used by researchers is qualitative. Based on data on the form of use of Javanese and Indonesian using data from the community of Dolok Kahean Village, Simalungun Regency, obtained using the listening method, namely listening to language use. Next, using the conversation method (interview), namely conducting conversations and contact between the researcher and the informant in the case of the language shift phenomenon, it was found that Javanese, which is the common language of the people of Dolok Kahean Village, Simalungun Regency, experienced a heavy shift. Adults, who still use Javanese actively, show dominant use of Indonesian in the form of language they use. Even though teenagers are able to understand Javanese, they no longer use Javanese actively, while children in Dolok Kahean village find it very difficult to understand Javanese and are no longer able to use Javanese. Another indication is the existence of the Indonesian language which should have replaced the existence of the Javanese language by Indonesian. This is very clearly seen by the passiveness of the children in Dolok Kahea village in using Indonesian.